2012
DOI: 10.1111/j.1365-2966.2011.20256.x
|View full text |Cite
|
Sign up to set email alerts
|

Very fast photometric and X-ray observations of the intermediate polar V2069 Cygni (RX J2123.7+4217)

Abstract: We present fast timing photometric observations of the intermediate polar V2069 Cygni (RX J2123.7+4217) using the Optical Timing Analyzer (OPTIMA) at the 1.3-m telescope of Skinakas Observatory. The optical (450-950 nm) light curve of V2069 Cygni was measured with sub-second resolution for the first time during 2009 July and revealed a double-peaked pulsation with a period of 743.38 ± 0.25 s. A similar double-peaked modulation was found in the simultaneous Swift satellite observations. We suggest that this per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Hence, these Xray periods and our shorter period conform to the spin period of the white dwarf. Although this spin period was already detected in optical light (Nasiroglu et al 2012), our measurement of the spin period should be considered as a new result because its precision is three orders of magnitude higher than the precisions of all other measurements of the spin period in V2069 Cyg. The longer period detected by us is the orbital sideband because it conforms to the formula: 1/P beat = 1/P spin − 1/P orb , where P orb is the orbital period found by Thorstensen and Taylor (2001).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Hence, these Xray periods and our shorter period conform to the spin period of the white dwarf. Although this spin period was already detected in optical light (Nasiroglu et al 2012), our measurement of the spin period should be considered as a new result because its precision is three orders of magnitude higher than the precisions of all other measurements of the spin period in V2069 Cyg. The longer period detected by us is the orbital sideband because it conforms to the formula: 1/P beat = 1/P spin − 1/P orb , where P orb is the orbital period found by Thorstensen and Taylor (2001).…”
Section: Discussionmentioning
confidence: 72%
“…8). Examining figure 6 in Nasiroglu et al (2012), we found out that in 2009 the spin pulse profile of V2069 Cyg was also double-peaked, where, in contrast with the spin pulse profile observed in 2014, two humps were equally pronounced. The reality of this pulse profile is confirmed by the power spectrum presented in figure 4 in Nasiroglu et al, which reveals the very strong first harmonic of the spin oscillation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Examples of results obtained with OPTIMA include e.g. pulsars (Słowikowska et al 2009), the first optical magnetar (Stefanescu et al 2008), intermediate polars (Nasiroglu et al 2012), polars (Słowikowska et al 2013) and a black hole candidate with optical variability (Kanbach et al 2001). Similar to previous years, we have conducted several observations of HU Aqr during our OPTIMA observing campaigns at the Skinakas Observatory (SKO) in 2011 and 2012 (Goździewski et al 2012;Słowikowska et al 2013).…”
Section: Observations With Optima In 2011 and 2012mentioning
confidence: 73%
“…Here, the first Tbabs component accounts for interstellar absorption, (PartCov*Tbabs) models the circumstellar absorption and Mekal is as before. As in Nasiroglu et al (2012), our first fit could not constrain the plasma temperature, but provided a lower limit of > 8 keV at the 3σ level. The resulting fit did not model the 6.7 keV Fe xxv line well, and had a χ 2 R = 1.04.…”
Section: X-raymentioning
confidence: 92%